Pengaruh Metode Sas (Struktural Analisis Sintesis) Tehadap Peningkatan Keterampilan Membaca Permulaan Pada Siswa Kelas II SDN Mappala Kecamatan Rappocini Kota Makassar - Ahmad Syawaluddin; Muhammad Faisal; Risal Risal (Publikasi Pendidikan, 2018)
Effect of Method SAS (Structural Analysis Synthesis) Toward Improved Reading Skills Starts in Class II SDN Mappala Rappocini District of Makassar. The problem in this research is still low ability students in beginning reading skills. The formulation of the problem is whether there are significant structural synthesis method of analysis (SAS) to increase reading skills at the beginning of second grade students of SDN Mappala Rappocini District of Makassar City ?. The purpose of this study was to determine the effect of structural synthesis method of analysis (SAS) to increase reading skills at the beginning of second grade students of SDN Mappala Rappocini District of the city of Makassar in the learning process. The approach used in this study is quantitative type of research is experimental, with Pre Test stage, treatment, and post test. The study design used is pre experimental design which is a form of research design one group Pre Test posttest design. The population and the sample was grade II SDN Mappala Rappocini District of the city of Makassar with enrollment of 30 students. Data collection techniques used is a test, documentation and observation. Data analysis technique used is the analysis of descriptive statistics, normality test, the hypothesis (t-test), and paired sample t-test. Early reading skills after giving treatment using SAS increases more than before the administration method of SAS in the learning process. After testing the hypothesis by using t-test showed that there were significant differences between the skills students memnaca starters. In conclusion SAS method provides a positive influence on students' reading skills at the beginning of class II.